Ultrastructure and Molecular Phylogeny of Iotanema spirale gen. nov. et sp. nov., a New Lineage of Endobiotic Fornicata with Strikingly Simplified Ultrastructure - Yubuki, Naoji; Zadrobílková, Eliška; Čepička, Ivan (The Journal of eukaryotic microbiology, 2017)
Fornicata (Metamonada) is a group of Excavata living in low-oxygen environments and lacking conventional mitochondria. It includes free-living Carpediemonas-like organisms from marine habitats and predominantly parasitic/commensal retortamonads and diplomonads. Current modest knowledge of biodiversity of Fornicata limits our ability to draw a complete picture of the evolutionary history in this group. Here, we report the discovery of a novel fornicate, Iotanema spirale gen. nov. et sp. nov., obtained from fresh feces of the gecko Phelsuma madagascariensis. Our phylogenetic analyses of the small subunit ribosomal RNA gene demonstrate that I. spirale is closely related to the free-living, marine strain PCS and the Carpediemonas-like organism Hicanonectes teleskopos within Fornicata. Iotanema spirale exhibits several features uncommon to fornicates, such as a single flagellum, a highly reduced cytoskeletal system, and the lack of the excavate ventral groove, but shares these characters with the poorly known genus Caviomonas. Therefore, I. spirale is accommodated within the family Caviomonadidae, which represents the third known endobiotic lineage of Fornicata. This study improves our understanding of character evolution within Fornicata when placed within the molecular phylogenetic context.
Keywords: Animals; Cytoskeleton; Microscopy, Electron, Transmission; RNA ribozomální; ribozomální DNA; feces; Feces; DNA, Ribosomal; parasite; taxonomy; cytoskelet; evolution; Metamonada; Caviomonadidae; Evolution, Molecular; molekulární evoluce; Phylogeny; RNA, Ribosomal; morphology; Lizards; Sequence Analysis, DNA; ještěři; transmisní elektronová mikroskopie; zvířata; sekvenční analýza DNA; fylogeneze; new taxa; Eukaryota